Technical Debt Management in Agile Software Development: A Systematic Mapping Study - Leite, Gilberto de Sousa; Vieira, Ricardo Eugênio Porto; Cerqueira, Lidiany; Maciel, Rita Suzana Pitangueira; Freire, Sávio; Mendonça, Manoel (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
Context: Agile methodologies use continuous delivery and adaptability to develop software that meets the needs of its users. However, such methods are prone to accumulate technical debt (TD). Agile teams must balance the benefits and risks of incurring debt by managing TD items. Knowing how TD management is conducted in agile software teams can help agile practitioners increase their ability to handle TD items. Aims: To investigate, based on the state of the art, how agile software teams have managed existing TD items in their projects. Method: We carried out a systematic mapping study covering 39 articles from 2010 to 2023. Results: Among the agile methodologies, Scrum was the most used for TD management. Regarding practices, agile teams employ mostly user stories and sprint backlogs to identify TD items. Sprints and sprint backlogs are used to monitor debt, while refactoring is applied to prevent and repay TD items. Conclusion: This study maps current knowledge on TD management in agile methodologies, serving as a starting point for new investigations in the area.